O potrzebie afiliacji jako pułapce w świecie mediów na przykładzie tekstów zamieszczanych w „Naszym Dzienniku” - Szymborska, Marta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The media, while fulfilling the needs of individuals, may also influence people. A fundamental and relevant psychological need is the desire for acceptance and, connected with it, the need for affiliation. The enhancement of self-esteem achieved by gaining support for the professed opinions, the feeling of security resulting from being a member of a particular group, which eliminates fear, may lead to conformism. The addressor, willing to influence the recipient, can refer to their common interpretative horizon, axiological agreement and common good, thus, by means of ingratiation, can bring about a change in the recipient`s attitude. The aim of the article is to indicate integrative linguistic devices applied by mass media which make the persuasive action easier. Referring to friendship makes persuasion and manipulation much more simple; opposing the community may result in exclusion.